Individual Counseling to Enhance Students' Academic Resilience Through the Sang Surya Psychological Service Unit - Septiani, Shilla Ninda; Rejeki, Asri (Jurnal Psikologi Terapan, 2024)
This study aims to improve students' academic resilience with individual counseling with goal setting techniques. A sample of 5 students as subjects were given treatment, namely counseling and observed after being given treatment. From the results of the pre-test, the results showed that the level of resilience of the subject was sufficient, between the ranges of 90-115. Furthermore, observations were made which showed significant behavioral changes. This means that counseling treatment with goal setting techniques can increase the subject's academic resilience. This finding is in line with previous research which shows that group counseling with cognitive restructuring techniques can increase students' academic resilience. By providing significant results but in this study there were no results from the post-test or comparison between groups.  The findings of this study can be a foundation for students that goal setting techniques can be applied to individual counseling to increase academic resilience. In the future, students can use research methods that compare between groups and can show significant results.